Achieving Provider Engagement: Providers' Perceptions of Implementing and Delivering Integrated Care. (December 2014) - Ignatowicz, Agnieszka; Greenfield, Geva; Pappas, Yannis; Car, Josip; Majeed, Azeem; Harris, Matthew
The literature on integrated care is limited with respect to practical learning and experience. Although some attention has been paid to organizational processes and structures, not enough is paid to people, relationships, and the importance of these in bringing about integration. Little is known, for example, about provider engagement in the organizational change process, how to obtain and maintain it, and how it is demonstrated in the delivery of integrated care. Based on qualitative data from the evaluation of a large-scale integrated care initiative in London, United Kingdom, we explored the role of provider engagement in effective integration of services. Using thematic analysis, we identified an evolving engagement narrative with three distinct phases: enthusiasm, antipathy, and ambivalence, and argue that health care managers need to be aware of the impact of professional engagement to succeed in advancing the integrated care agenda.